Vacunación contra el neumococo en niños menores de 5 años : análisis de costo beneficio (2021)
Objective: To estimate, from the perspective of the Colombian health system, the cost-benefit relationship of PCV 13 vaccination compared to PCV 10 vaccination for the cohort of children under 5 years of age in Colombia. Methods: A Markov model was built, in which the different protections and pathologies related to pneumococcal infection were modeled during the first 5 years of life, in which the investment costs were determined with each of the strategies (vaccine PCV 13 and PCV10) and the costs associated with the outcomes of each of the interventions to determine the costs and benefits of the two vaccination strategies available in the country. A literature search was carried out to identify clinical studies and extract general disease parameters and the calculation of the probabilities of each clinical outcome. The time horizon was 5 years. A 3% discount rate was applied. All monetary units are expressed in Colombian pesos...